Clinical, Radiological, and Endoscopic Ultrasound Findings in Groove Pancreatitis: A Multicenter Retrospective Study - Okasha, Hussein Hassan; Gouda, Mohamed; Tag-Adeen, Mohammed; Farouk, Mahmoud; Alzamzamy, Ahmed; Elenin, Sameh Abou; Pawlak, Katarzyna M.; Awad, Abeer; Mohamed, Borahma (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Groove pancreatitis is a rare form of focal pancreatitis that affects the groove area. Since groove pancreatitis may be mistaken for malignancy, it should be considered in patients with pancreatic head mass lesions or duodenal stenosis to avoid unnecessary surgical procedures. The aim of the study was to document the clinical, radiologic, endoscopic characteristics, and treatment outcomes of patients with groove pancreatitis. Materials and Methods: This retrospective multicenter observational study included all patients diagnosed with one or more imaging criteria suggestive of groove pancreatitis in the participating centers. Patients with proven malignant fine-needle aspiration/biopsy results were excluded. All patients were followed in their own centers and were retrospectively evaluated. Results: Out of the initially included 30 patients with imaging criteria suggestive of groove pancreatitis, 9 patients (30%) were excluded because of malignant endoscopic ultrasound fine-needle aspiration or biopsy results. The mean age of the included 21 patients was 49 ± 10.6 years, with a male predominance of 71%. There was a history of smoking in 66.7% and alcohol consumption in 76.2% of patients. The main endoscopic finding was gastric outlet obstruction observed in 16 patients (76%). There was duodenal wall thickening in 9 (42.8%), 5 (23.8%), and 16 (76.2%) patients on computed tomography, magnetic resonance imaging, and endoscopic ultrasound, respectively. Moreover, pancreatic head enlargement/mass was observed in 10 (47.6%), 8 (38%), and 12 (57%) patients, and duodenal wall cysts in 5 (23.8%), 1 (4.8%), and 11 (52.4%) patients, respectively. Conservative and endoscopic treatment has achieved favorable outcomes in more than 90% of patients. Conclusion: Groove pancreatitis should be considered in any case with duodenal stenosis, duodenal wall cysts, or thickening of the groove area. Various imaging modalities, including computerized tomography, endoscopic ultrasound, and magnetic resonance imaging, have a valuable role in characterizing groove pancreatitis. However, endoscopic fine-needle aspiration or biopsy should be considered in all cases to diagnose groove pancreatitis and exclude malignancy, which can have similar findings. Cite this article as: Okasha HH, Gouda M, Tag-Adeen M, et al. Clinical, radiological, and endoscopic ultrasound findings in groove pancreatitis: A multicenter retrospective study. Turk J Gastroenterol. 2023;34(7):771-778.